Synthesis of Sargassum char-supported Ni-Fe nanoparticles and its application in tar cracking during biomass pyrolysis. (1st September 2020) - Liang, Shuang; Guo, Feiqiang; Du, Shilin; Tian, Beile; Dong, Yichen; Jia, Xiaopeng; Qian, Lin
Graphical abstract: Highlights: Sargassum char-supported Ni-Fe NPs were synthesized for tar cracking. The char support possesses high surface area with unique structures. Well-dispersed Ni NPs and FeNi3 NPs were in situ formed. The tar conversion efficiency reached 90.07% at 600 °C for SC@0.1Ni-Fe. The catalysts exhibited good stability during the five times reuse. Abstract: Ni-Fe nanoparticles (NPs) supported on biomass char were synthesized by a pyrolysis method using an abundant and fast-growing seaweed biomass ( Sargassum ) as the precursor for biomass tar cracking applications. With the presence of Ni and Fe ions, the surface area of the prepared SC@0.0.05Ni-Fe and SC@0.1Ni-Fe was larger than 200 m 2 g −1 with unique honeycomb-like structures, which was conducive to improving the absorption capacity of the catalyst to tar molecules, enhancing the interaction between tar molecules and active sites, and prolonging the reaction time. Well-dispersed Ni NPs and FeNi3 NPs were in situ formed on the surface of the char support during Sargassum pyrolysis. At a low temperature of 600 °C, the fresh SC@0.1Ni-Fe reached a high tar conversion efficiency of 90.07% with a significant increase in the syngas yield. The yields of the combustible gas components (H2, CO, and CH4 ) were significantly improved as a result of the tar cracking. After five times successive reuse under the same conditions, the SC@0.1Ni-Fe was able to maintain the tar conversion efficiency at a level of higher than 80%. The structure of the char-supported Ni-Fe catalysts was well retained with the change of the honeycomb-like structure to a certain extent, ensuring the high stability of the catalyst.